2017
DOI: 10.3390/molecules22020214
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics Studies of 12 Alkaloids in Rat Plasma after Oral Administration of Zuojin and Fan-Zuojin Formulas

Abstract: Zuojin formula (ZJ) is a traditional Chinese medicine (TCM) prescription consisted of Coptidis Rhizoma (CR) and Euodiae Fructus (EF), and has been used to treat gastrointestinal (GI) disease for more than 700 years. Fan-Zuojin formula (FZJ) is a related TCM prescription also consisted of CR and EF with the opposite proportion. In recent years, ZJ was getting more attention for its antitumor potential, but the indeterminate pharmacokinetic (PK) behavior restricted its clinical applications, and the PK differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…In the current study, multiple absorption peaks were observed in plasma concentration–time curves of berberine and coptisine after oral administration of BXD to rats, which were once thought to be due to enterohepatic circulation and tissue distribution accompanied by blood re‐absorption in rats. However, research findings are suggesting that the site‐specific absorption instead of enterohepatic circulation could be the major reason for the multi‐peak phenomenon of berberine and coptisine (Li, Lin, et al, ; Li, Ren, et al, ; Li, Zhang, et al, ; Qian, Zhang, Yang, Xu, & Yang, ; Tan, Guo, & Zhong, ). Comparing dose‐modified C max and AUC (0 –t ) values (Table ) of berberine and coptisine with the previous pharmacokinetic studies (Feng et al, ; Qian et al, ), it was repeatedly found that the absorption of the alkaloids was greatly improved in herbal prescriptions.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, multiple absorption peaks were observed in plasma concentration–time curves of berberine and coptisine after oral administration of BXD to rats, which were once thought to be due to enterohepatic circulation and tissue distribution accompanied by blood re‐absorption in rats. However, research findings are suggesting that the site‐specific absorption instead of enterohepatic circulation could be the major reason for the multi‐peak phenomenon of berberine and coptisine (Li, Lin, et al, ; Li, Ren, et al, ; Li, Zhang, et al, ; Qian, Zhang, Yang, Xu, & Yang, ; Tan, Guo, & Zhong, ). Comparing dose‐modified C max and AUC (0 –t ) values (Table ) of berberine and coptisine with the previous pharmacokinetic studies (Feng et al, ; Qian et al, ), it was repeatedly found that the absorption of the alkaloids was greatly improved in herbal prescriptions.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional Chinese anti-diabetic formula, Jinqi formula (Coptidis rhizoma, Astragali rhadix and Lonicerae japonicae Flos) could inhibit TG accumulation [ 85 ]. Zuojin and Fan-Zuojin formulas with reverse mixture ratios of CR and Euodiae fructus led to different interactions on the in vitro absorption of alkaloids and opposite effects [ 86 , 87 ]. Ge-Gen-Qin-Lian-Tang could decrease lipid formation [ 88 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Other structural analogs were reported in a previous study (Sun et al, ). This might be due to the inhibition of berberine on gastrointestinal motility (Qian, Zhang, Yang, Xu, & Yang, ).…”
Section: Resultsmentioning
confidence: 99%